Association between physical activity and frailty transitions in middle-aged and older adults: a nationwide longitudinal study - Huang, Li; Liang, Zhenzhen; Chen, Huajian (International journal of behavioral nutrition and physical activity, 2025)
Frailty has become an important health problem in the middle-aged and older people population. Physical activity (PA) is a key intervention for frailty prevention and management. However, studies of the association between COVID-19 pre-pandemic PA and the worsening or improvement of frailty during the pandemic remain unclear. This longitudinal cohort study used data from the English Longitudinal Study of Ageing (ELSA), including participants aged 50 and over. Three intensities of PA (vigorous, moderate, and mild) were categorized as less than once per week and at least once per week, respectively, based on participant self-report. The frailty index (FI) assessed the frailty status, defining frailty as FI ≥ 25. Logistic regression was applied to examine the association between PA and frailty, estimating odds ratios (OR) and 95% confidence intervals (95% CI). Of the 4379 non-frail participants at baseline (median age 67, 54.9% female), 8.1% developed frailty during a mean follow-up of 3.5 years. Among 564 frail participants at baseline (median age 71, 66.5% female), 17.9% regained health. Compared to those engaging in PA less than once per week, participants who engaged in vigorous (OR: 0.47 [95% CI: 0.35-0.62]), moderate (OR: 0.37 [95% CI: 0.29-0.48]), or mild (OR: 0.38 [95% CI: 0.26-0.56]) PA at least once a week had a lower risk of frailty worsening. Additionally, participants who engaged in moderate (OR: 2.04 [95% CI: 1.29-3.21]) or mild (OR: 2.93 [95% CI: 1.54-5.58]) PA at least once a week had a higher likelihood of frailty improvement. Sensitivity analyses based on comprehensive PA levels confirmed these findings. Participants who maintained at least one PA per week had lower frailty worsening (Vigorous, OR: 0.20 [95%CI: 0.12-0.33]; Moderate, OR: 0.13 [95%CI: 0.09-0.19]; Mild, OR: 0.20 [95%CI: 0.11-0.38]) and higher frailty improvement rates (Moderate, OR: 3.43 [95%CI: 1.93-6.11]; Mild, OR: 4.65 [95%CI: 1.90-11.42]). In addition, individuals (Vigorous, OR: 0.35 [95%CI: 0.20-0.60]; Moderate, OR: 0.36 [95%CI: 0.22-0.56]) who transitioned from inactive to active also exhibited a lower risk of frailty. This study emphasized the critical role of PA in preventing and improving frailty in middle-aged and older people, especially during the COVID-19 pandemic. Our study also highlighted the importance of maintaining PA habits to reduce frailty risk and promote its improvement. Also, the study indicated that individuals who transitioned from inactive to active had a lower risk of frailty. These findings enriched the understanding of the association between PA and frailty and provided valuable insights for addressing the health impact of future pandemics on middle-aged and older people.
Gesehen am 22.08.2025